The Radial Velocity Experiment (RAVE): fifth data release - Kunder, Andrea; Grebel, Eva K. (The astronomical journal, 2017)
Data Release 5 (DR5) of the Radial Velocity Experiment (RAVE) is the fifth data release from a magnitude-limited ( ##IMG## [http://ej.iop.org/images/1538-3881/153/2/75/ajaa5184ieqn1.gif] $9\lt I\lt 12$ ) survey of stars randomly selected in the Southern Hemisphere. The RAVE medium-resolution spectra ( ##IMG## [http://ej.iop.org/images/1538-3881/153/2/75/ajaa5184ieqn2.gif] $R\sim 7500$ ) covering the Ca-triplet region (8410-8795 Å) span the complete time frame from the start of RAVE observations in 2003 to their completion in 2013. Radial velocities from 520,781 spectra of 457,588 unique stars are presented, of which 255,922 stellar observations have parallaxes and proper motions from the Tycho- Gaia astrometric solution in Gaia DR1. For our main DR5 catalog, stellar parameters (effective temperature, surface gravity, and overall metallicity) are computed using the RAVE DR4 stellar pipeline, but calibrated using recent K2 Campaign 1 seismic gravities and Gaia benchmark stars, as well as results obtained from high-resolution studies. Also included are temperatures from the Infrared Flux Method, and we provide a catalog of red giant stars in the dereddened color ##IMG## [http://ej.iop.org/images/1538-3881/153/2/75/ajaa5184ieqn3.gif] $(J-Ks)_0$ interval (0.50, 0.85) for which the gravities were calibrated based only on seismology. Further data products for subsamples of the RAVE stars include individual abundances for Mg, Al, Si, Ca, Ti, Fe, and Ni, and distances found using isochrones. Each RAVE spectrum is complemented by an error spectrum, which has been used to determine uncertainties on the parameters. The data can be accessed via the RAVE Web site or the VizieR database.